THE EFFECT OF ANAGRAM GAMES ON SECONDARY LEVEL STUDENTS’ READING ACHIEVEMENT - Endang Sulistianingsih; Rizki Dwi Juliani; Toto Pradjarto (Universitas Bengkulu, 2020)
The study employed a quantitative approach with Two-Group Design. The population consisted of six classes. We took a sample of two classes, VII-C as the experimental group and VII-D as the control group. Samples were determined using cluster sampling techniques. Based on the writer’s observation, some teachers in Junior High School Tegal still used the conventional technique in teaching especially in teaching reading, in fact, reading is very difficult to teach in Junior High School because a lack of vocabulary made the students’ motivation declined in reading. The result of the study revealed the use of Anagram was effective in teaching and learning reading. It happened since in Anagram implementation the students as the participants and the teacher as the facilitator. This situation was suited to the curriculum 2013 in which it concerned students oriented. Besides the students had fun and enjoyed reading because they teach each other, it easy to known students’ lack and need by Anagram Games, students trained to dare to ask and give their opinion especially in leaning reading which has many words and paragraphs. This method is easier, useful and flexible for the teacher to apply because of no need for a lot of time, media, realia and place. So, this study gives recommendations for teachers and students to implement this method.